A feeding circuit with CPW for CA-RLSA. - Ronghong Jin (IEEE Transactions on antennas and propagation)
For a concentric array radial line slot antenna (CA-RLSA) with a boresite beam, a rotating mode should be excited. A planar feeding circuit exciting a rotating mode in a parallel-plate waveguide is proposed in this paper. The structure consists of a coplanar waveguide (CPW), ring slot, and cavity, which is planar and suitable for integrating and minimizing even in a millimeter-wave band. The experimental results agree well with the simulation